INTEGRATING TECHNOLOGY IN EFL CLASSROOM FOR INDONESIAN ADOLESECENT LEARNERS - Murah Harfani Batubara (Universitas Islam Sumatera Utara (UISU), 2021)
The coming of the internet and the advancement of technology make revolution in Language Pedagogy, especially in the EFL classroom. Teaching the students who were born as the digital natives forces EFL, teachers have to integrate technology in language teaching. This article was written based on a recent EFL teacher’s practice. This study employed a case study method with 30 students of grade 9 of Junior High School in the west part of Indonesia as the participants. The aim of this study was to elaborate the way how the teacher made the students more familiar with the computer and the internet access in EFL Classroom. A Messenger Group as the main communication platform, supported by other web-based platforms including school’s Facebook (FB) group and online materials were integrated into learning activities. The findings showed that students found using technology in the classroom was easy due to the teacher’s instruction. They also reported that the technology integration in their EFL classroom encouraged their creativity and helped to accommodate their diverse interest. As a result, the students feel more comfortable and confident using technology for educational purposes and, become more creative and innovative in doing their project. Beside the clear instructions from the teacher, the availability of the computer laboratory, internet access, and students’ smartphones really help the success of this course.